What factors determine the number of trading partners? - Noriaki Matsushima; Ryusuke Shinohara (Osaka University, Institute of Social and Economic Research (ISER), 2011)
The purpose of the paper is to provide a simple model explaining buyer-supplier relationships and show what factors determine the number of trading partners. We show that when the supplier is able to determine the number of trading partners, the optimal number is small if the supplier's bargaining power with them is weak, the economy of scope in the supplier's variable costs is significant, and that in its sunk investment is weak. Investment may be greater when the number of trading partners is small. The results may be consistent with the formation of Japanese buyer-supplier relations.
Keywords: L14; M11; 330; buyer; supplier; investment; economies of scope; Lieferantenmanagement; Verbundvorteil; Investition; Variable Kosten; Japan